The Last Dualism: Life and Death in Goddess Feminist Thealogy - Christ, Carol P. (Journal of feminist studies in religion, 2011)
This essay is a reflection on Valerie Saiving's statement that the "last dualism," the dualism between life and death, is the root of all the other dualisms and will be the most difficult for feminists to overcome. Carol Christ agrees with Saiving that the fear of death is at the root of all the dualisms and that the assumption that the enduring individual is of the highest value is reason that death is not accepted. She suggests that rituals of giving and receiving in ancient and traditional Crete embody an understanding of the self as embedded in a matrix of interdependent relationships. This insight is also expressed in the symbols of the spiral and the circle dance. Analysis of their burial rituals suggests that ancient Cretans affirmed the death of the individual while celebrating the continuation of life for others. An understanding of the self as interdependent in the matrix of life combined with an acceptance of individual death is also found in process philosophy. Carol Christ, like Saiving, argues that process philosophy provides an appropriate undergirding for feminist philosophies and theologies. Goddess symbols and rituals of ancestor connection celebrate the interdependence of life. From this standpoint, individual death can be embraced and the survival of life for future generations can be promoted. The "last dualism" is overcome.